Role of multimeric analysis of von Willebrand factor (VWF) in von Willebrand disease (VWD) diagnosis: Lessons from the PCM-EVW-ES Spanish project. - Almudena Pérez-Rodríguez; Javier Batlle; Irene Corrales; Nina Borràs; Ángela Rodríguez-Trillo; Esther Lourés; Ana Rosa Cid; Santiago Bonanad; Noelia Cabrera; Andrés Moret; Rafael Parra; María Eva Mingot-Castellano; et al. (PLoS ONE)
The multimeric analysis (MA) of plasma von Willebrand factor (VWF) evaluates structural integrity and helps in the diagnosis of von Willebrand disease (VWD). This assay is a matter of controversy, being considered by some investigators cumbersome and only slightly informative. The centralised study 'Molecular and Clinical Profile of von Willebrand Disease in Spain (PCM-EVW-ES)' has been carried out by including the phenotypic assessment and the genetic analysis by next generation sequencing (NGS) of the VWF gene (VWF). The aim of the present study was to evaluate the role of MA to the diagnosis of these patients and their potential discrepancies. Two hundred and seventy out of 480 patients centrally diagnosed with VWD had normal multimers, 168 had abnormal multimers and 42 a total absence of multimers. VWF MA was of great significance in the diagnosis of 83 patients (17.3%), it was also of help in the diagnosis achieved in 365 additional patients (76%) and was not informative in 32 cases (6.7%). With regard to discrepancies, 110 out of 480 (23%) patients centrally diagnosed with VWD presented some kind of discordance between VWF:RCo/VWF:Ag and/or VWF:CB/VWF:Ag ratios, multimeric study and/or genetic results. The VWF MA was key in the presence of novel mutations as well as in cases with phenotypic discrepancies. A comparison between the contribution of MA and VWF:CB showed a clearly higher contribution of the former in the diagnostic process. These data seem to reinforce the relevance of the VWF MA in VWD diagnosis, despite all its limitations.